Optimizing The Performance Of Village-Owned Enterprises Through Human Resource Management - Sandra Kaitlyn Sigrid (International Forum of Researchers and Lecturers, 2025)
This research aims to analyze optimal strategies for improving the performance of Village-Owned Enterprises (BUMDes) through human resource management (HR). A qualitative approach was used by collecting data through interviews and documentation studies. The research results show that effective HR management can make a significant contribution to improving the performance of BUMDes. Factors such as selective recruitment, training and development, and good performance management are the keys to achieving optimization of BUMDes performance. The implication of this research is the importance of greater attention to HR management in the context of BUMDes development.